2007
DOI: 10.1111/j.1469-8137.2007.02191.x
|View full text |Cite
|
Sign up to set email alerts
|

The mycorrhiza helper bacteria revisited

Abstract: Contents Summary 22 Introduction 23 Evidence for the occurrence of MHB 23 Ecological and evolutionary implications of MHB 23 The question of MHB specificity 27 Mechanisms of the MHB effect 28 Role of MHB in mycorrhizal functions 31 Conclusions and research priorities 32 References  33 Summary In natural conditions, mycorrhizal fungi are surrounded by complex microbial communities, which modulate the mycorrhizal symbiosis. Here, the focus is on the so‐called ‘mycorrhiza helper bacteria’ (MHB). This concept … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
556
1
13

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 788 publications
(581 citation statements)
references
References 118 publications
(161 reference statements)
11
556
1
13
Order By: Relevance
“…Differences in plant exudation patterns between plants species is thought to exert differential selection in the rhizosphere, thereby shaping the size and structure of soil-borne communities (Bardgett et al, 1999;Smalla et al, 2001;Kowalchuk et al, 2002). The AMF infections are also known to affect exudation patterns (Frey-Klett et al, 2007), and the differential mycorrhizal status of the two plants in our study (F. rubra is mycorrhizal whereas C. arenaria is not; Greipsson and El-Mayas, 1999;Orlowska et al, 2005) may have contributed to differences in observed exudation patterns. The results with respect to trehalose exudation are of particular relevance in this respect, as this disaccharide is an important product of AMF.…”
Section: Antibiotic-production Genesmentioning
confidence: 52%
See 1 more Smart Citation
“…Differences in plant exudation patterns between plants species is thought to exert differential selection in the rhizosphere, thereby shaping the size and structure of soil-borne communities (Bardgett et al, 1999;Smalla et al, 2001;Kowalchuk et al, 2002). The AMF infections are also known to affect exudation patterns (Frey-Klett et al, 2007), and the differential mycorrhizal status of the two plants in our study (F. rubra is mycorrhizal whereas C. arenaria is not; Greipsson and El-Mayas, 1999;Orlowska et al, 2005) may have contributed to differences in observed exudation patterns. The results with respect to trehalose exudation are of particular relevance in this respect, as this disaccharide is an important product of AMF.…”
Section: Antibiotic-production Genesmentioning
confidence: 52%
“…The results with respect to trehalose exudation are of particular relevance in this respect, as this disaccharide is an important product of AMF. Trehalose has also been implicated in the selection of potential mycorrhizal helper bacteria, including several Pseudomonas and Burkholderia species (Frey-Klett et al, 2007), although it is premature to conclude that the observed changes in these genera are related to this function. The AMFs have been implicated as major conduits for C translocation from plants into the soil under different atmospheric CO 2 conditions, and our previous observation that the mycorrhizal plant (F. rubra) exerted greater influence on bacterial and fungal communities is consistent with this assertion (Drigo et al, 2007).…”
Section: Antibiotic-production Genesmentioning
confidence: 99%
“…These associations could be a product of trophic interactions between predatory protists and their bacterial prey [45], a product of direct symbioses (e.g. the relationships between fungi and bacteria [46]), or simply shared environmental drivers. The shared biogeographic patterns of prokaryotic and eukaryotic communities demonstrates that there are numerous direct and indirect associations between soil organisms, and unravelling these relationships will be critical to building a more integrated understanding of below-ground ecology.…”
Section: Results and Discussion (A) Central Park Soil Diversity Is Nomentioning
confidence: 99%
“…The greenalgal strain is massively enriched within the fungal structures, while cyanobacterial Nostoc strains are acquired from the surfaces of L. pulmonaria recurrently during the life-time of the thallus to form internal organs devoted to nitrogen fixation in lichens (Hyvärinen et al, 2002, Cornejo andScheidegger, 2013). Conversely, the external presence of other bacteria in the lichen symbiosis recalls the helper bacteria of mycorrhizal symbioses, which provide multiple functions to mutually support and stabilize the root symbioses, including exchange of carbohydrates and vitamin provision (Frey-Klett et al, 2007;Deveau et al, 2010). The long-living lichen thallus is formed by tightly packed fungal hyphae, which are conglutinated by their cell walls.…”
Section: Discussionmentioning
confidence: 99%